Incidental finding of a giant asymptomatic right atrial tumor - Strecker, Thomas (e-Century Publishing Corporation, 2014)
Primary cardiac tumors are very rare, atrial myxoma being the most common benign tumor of the heart. They may present with a great variety of incidental asymptomatic masses to severe life-threatening cardiovascular complications necessitating emergency surgery. Here we report the diagnostic evaluation and successful surgical resection of such a giant cardiac tumor which was found on a routine medical check-up in a 62-year-old patient. Histology confirmed diagnosis of unusually huge myxoma. This article demonstrates it’s necessary to include cardiac tumors in the differential diagnosis of subtle and non-specific cardiothoracic symptoms.